ANALISIS PROBABILITAS PENERJEMAHAN VERBA POTENSIAL DALAM KOMIK DETEKTIF CONAN SERI 66 KARYA AOYAMA GOSHO - PRAKOSA, GELAR (Jurnal Ilmiah Mahasiswa FIB, 2013)
This paper studies the Indonesian translation probability of a comic. The data source is a Japanese comic, detective Conan serial 66 by Aoyama Gosho. Thus, the result of the study was: There were 27 Japanese potencial verbs to be found in Detective Conan serial 66 by Aoyama Gosho. And the equivalent of bisa are 14 verb, dapat 1 verb, and 12 verbs untranslated.The percentages of probability are 0.51 for bisa, 0.03 for dapat, and 0.44 for untranslated verbs.   Key Word: Comic, Translation, Kanou Hyougen, Kanou Doushi, Probability.